Sosialisasi Pengenalan Konsep Budgeting sebagai Dasar Perencanaan Keuangan Siswa di SMKN 1 Ciruas - Suhartini Suhartini; Khusnul Khotimah; Jazilah Syifaurrohmah; Mohamad Arman; Siti Kartika (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This Community Service Program (PKM) was conducted on April 23, 2026, at SMKN 1 Ciruas under the title "Socialization of the Budgeting Concept as a Foundation for Students' Financial Planning at SMKN 1 Ciruas." The program was motivated by students' limited understanding of personal financial management in the digital era, as reflected in increasing consumerism and inadequate financial planning, particularly in budgeting. The objective of this activity was to enhance students' understanding of the importance of budgeting as the foundation of financial planning. The program was implemented through several stages, including socialization, material presentation, pre-test, post-test, and interactive evaluation to measure participants' improvement in understanding. The activity involved 32 accounting students, one supervising lecturer, and two teacher representatives from SMKN 1 Ciruas. The results showed a significant improvement in students' understanding based on the comparison between the pre-test and post-test scores. Understanding of budgeting concepts increased from 50% to 90%, financial management skills from 45% to 85%, understanding of needs and wants from 55% to 88%, and knowledge of digital financial applications from 40% to 82%. These findings indicate that the program was successfully implemented and effectively improved students' financial literacy. Further activities, such as digital budgeting workshops and continuous mentoring, are recommended to encourage students to apply budgeting concepts consistently in their daily lives.